2015
DOI: 10.1016/j.vaccine.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Association between mixed rotavirus vaccination types of infants and rotavirus acute gastroenteritis

Abstract: Introduction Rotavirus remains the leading cause of severe diarrhea in children under 5 years worldwide. In the US, Rotarix® (RV1) and RotaTeq® (RV5), have been associated with reductions in and severity of rotavirus disease. Studies have evaluated the impact of RV1 or RV5 but little is known about the impact of incomplete or mixed vaccination upon vaccine effectiveness. Methods Case control study to examine association of combined RV1 and RV5 and rotavirus acute gastroenteritis, factoring severity of diarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…In the USA, combined vaccine effectiveness for full RV1 and RV5 vaccines was 80% in children younger than 8 years old [ 68 ]. In the USA, Mohammed et al [ 69 ] showed that children were still protected if they received combined vaccines (single vaccine OR 0.21 vs combined OR 0.29). In Belgium, hospitalizations declined in children younger than 2 years old, in the first year after vaccination (65%) and the second year after vaccination (80%) [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the USA, combined vaccine effectiveness for full RV1 and RV5 vaccines was 80% in children younger than 8 years old [ 68 ]. In the USA, Mohammed et al [ 69 ] showed that children were still protected if they received combined vaccines (single vaccine OR 0.21 vs combined OR 0.29). In Belgium, hospitalizations declined in children younger than 2 years old, in the first year after vaccination (65%) and the second year after vaccination (80%) [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the introduction of rotavirus vaccines such as Rotavac ® and Rotasiil ® , further vaccine development [53] and the impact of different vaccines on the herd immunity, it is mandatory to monitor virus variability [54]. A previously published study investigated the effectiveness of mixed rotavirus vaccinations [55]. Administration of mixed vaccines will pose a challenge for discrimination between wild-type RVA and vaccine strains in the future.…”
Section: Discussionmentioning
confidence: 99%